LAW ENFORCEMENT AGAINST CRIMINAL ACTS FRAUD IN FINANCIAL TRANSACTIONS BASED ON LAW NO. 10 OF 2010 CONCERNING BANKING - Kesuma, Moch Wisnu Pujaka; Nuraeny, Henny; Aridhayandi, M. Rendi (DE'RECHTSSTAAT, 2024)
Fraud is an unlawful act of fraud that is carried out intentionally and can harm other parties. Fraud can be in the form of theft, robbery, extortion, forgery, embezzlement and so on. Lay people usually say that fraud is a criminal act or an act of corruption. One case of criminal or fraud that occurred was a problem involving one of the BRI Bank employees with a customer in Cikeas. This case began with a report handled by Subdit II Reskrimsus Polda Riau No. LP/B290/VI/2022/SPKT in 2022. The purpose of this study is to determine law enforcement against criminal acts of fraud in banking transactions and to determine the factors that hinder law enforcement against criminal acts of fraud in banking transactions. The method used is sociological legal research, namely examining the applicable legal provisions and what happens in reality in society or to obtain clarity and understanding and research problems based on existing realities or case studies. The results of this study are the weak role of banking in efforts to overcome or participate in handling banking cases themselves, in addition to the problem of proving cases, doubts from investigators in determining whether there is a crime of money laundering as a continuation of banking crimes, and incomplete reports obtained by investigators so that investigators must re-examine the reported allegations. Suggestions The need to improve the quality of law enforcement officers by providing a deep understanding of fraud crimes in banking financial transactions.